1977
DOI: 10.1002/ar.1091880210
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the rat harderian gland by adrenergic and cholinergic nerve fibres

Abstract: The innervation of the rat Harderian gland was studied using histochemical methods for catecholamines and acetylcholinesterase (AChE). Selective denervations were performed to investigate the neural connections of this gland with various ganglia. Light microscopically the AChE-positive nerves seemed to run as thick bundles in the intertubular connective tissue. These bundles sent finer branches around the acini. The blood vessels, localized in the connective tissue septa, were surrounded by a dense plexus of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…However, in rabbits and hamsters, nerve terminals are in contact either with secretory or myoepithelial cells (Sakai 1981). Denervation experiments of Huhtala et al (1977) revealed that nerve terminals associated with end-pieces are cholinergic in nature, and of parasympathetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rabbits and hamsters, nerve terminals are in contact either with secretory or myoepithelial cells (Sakai 1981). Denervation experiments of Huhtala et al (1977) revealed that nerve terminals associated with end-pieces are cholinergic in nature, and of parasympathetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Huhtala et al (1977) also observed AchE-positive nerves along the blood vessels of the rat Harderian gland, while Norvell and Clabough (1972) did not find such in the hamster. The latter authors suggested that the modification of blood flow in the hamster gland is mainly due to adrenergic fibers.…”
Section: Innervationsmentioning
confidence: 92%
“…meridianus (Sakai and Yohro, 1981). Huhtala et al (1977) demonstrated that the rat Harderian gland receives both cholinergic and adrenergic nerves. The clear vesicles contained in the nerve endings located just outside the basal lamina of the tubules may release transmitter substances which diffuse through the basal lamina and may stimulate myoepithelial cells, epithelial cells, or both, promoting the release of the glandular secretion.…”
Section: Connective Tissuementioning
confidence: 99%